2017
DOI: 10.15580/gjms.2017.5.100217143
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of E-health among Health Care Providers in Kuwait

Abstract: Background:The nature and functions of e-health services are expanding rapidly and have the potential of not only improving health, but also to reduce health care costs, enhance scientific understanding of health issues, increase equity of health care, and improve communication between health care providers and patients. Objectives: The aim of the present study is to highlight e-health knowledge, attitude and practice among health care providers in Kuwait. Methods: This study was carried out in the 6 general h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…37 In this study, about 128 (49.2%) of respondents have good knowledge about utilization of DHIS(95% CI: [43, 55.3]) which was lower than the study conducted in Kenya. 38 The result of this study was also inconsistent with the study conducted in Kuwait 39 though consistent with the study conducted in South Africa. 36 But the result of this study was greater than the study conducted in Liberia.…”
Section: Discussionmentioning
confidence: 46%
“…37 In this study, about 128 (49.2%) of respondents have good knowledge about utilization of DHIS(95% CI: [43, 55.3]) which was lower than the study conducted in Kenya. 38 The result of this study was also inconsistent with the study conducted in Kuwait 39 though consistent with the study conducted in South Africa. 36 But the result of this study was greater than the study conducted in Liberia.…”
Section: Discussionmentioning
confidence: 46%
“…In this study, majority of the participants could correctly define EMR which is in synergy with the findings of studies conducted in Nigeria and Kuwait. 19 , 21 This finding could be attributable to the fact that this study was conducted in a tertiary health institution where continuous medical education is a pre-requisite for constancy of engagement and renewal of annual practising licenses which may have endeared them to acquiring information on EMRs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Ethiopia, Kuwait and Nigeria reported similar findings though slight variations existed in the methodology of assessment used. 19 , 20 , 22 , 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 23 , 24 Issues such as user adoption (satisfaction and ease of use), training, privacy and security were the major issues identified that are influencing the implementation of e-health applications in GCC member states. 25 , 26 Trust, health literacy, internet literacy and users’ attitudes were other factors affecting e-health adoption in Bahrain 27 and Kuwait. 28…”
Section: Literature Reviewmentioning
confidence: 97%